Tingkat Pengetahuan Mahasiswa Olahraga di Kabupaten Ngawi terhadap Pencegahan dan Penanganan Cedera Olahraga - Asyhari, Adithya Jeni Muchlis; Utomo, Andy Widhiya Bayu; Septianingrum, Kartika (Universitas Hamzanwadi, 2025)
Sports injuries are a significant problem that can affect the long-term health and performance of athletes. This study aims to analyze the level of knowledge of sports students in Ngawi Regency about the prevention and management of sports injuries, as well as the factors that influence it. This study used a quantitative design with a descriptive approach, with the main instrument being a structured questionnaire distributed to 200 sports students enrolled in universities in Ngawi Regency. The results showed that the majority of respondents had a sufficient level of knowledge, but there were still a large number of students who had insufficient knowledge about sports injuries. Age and gender were found to have an influence on students' knowledge level, where older and male students tended to have better knowledge compared to younger and female students. Based on these results, this study recommends the enhancement of a more comprehensive education and training programme in the sports education curriculum, which includes injury prevention techniques, use of protective equipment, and first aid. A more structured and evidence-based education programme could improve students' understanding of sports injuries and help reduce the incidence of injuries in sporting activities.